PERENCANAAN PENGEMBANGAN KURIKULUM PADA KULLIYATUL MU’ALLIMIEN AL-ISLAMIYAH - Nur Widia Wardani; Maisyaroh Maisyaroh; Ali Imron (Graduate School of Universitas Negeri Malang, 2016)
Curriculum Development Planning Kulliyatul Mu'allimien Al-Islamiyah. The purpose of this study are: (1) identify curriculum development planning; (2) identify curriculum development process; (3) determine the factors supporting and curriculum development planning; and (4) determine the strategy to overcome the inhibiting factors curriculum development planning. This study used a qualitative approach to describe the planning of curriculum development at Kulliyatul Mu'allimien Al-Islamiyah. The design of the study is a multi-site study means combining multiple sites, subject, background, and the scene is different. The key instrument is the researchers themselves, with the source of the research that led cottage, a team of curriculum developers, teachers, and students. Data obtained through observation, interviews, and documentation. The validity of the data that has been analyzed using the criteria of the credibility of the data with the triangulation of data sources. The results of the research, that the planning of curriculum development at KMI is aimed at character building through micro teaching, improvement of skills of students and teacher competence that leads to the career development of teachers.Perencanaan Pengembangan Kurikulum Kulliyatul Mu’allimien Al-Islamiyah. Tujuan penelitian ini adalah: (1) mengidentifikasi perencanaan pengembangan kurikulum;(2) mengidentifikasi proses pengembangan kurikulum ; (3) mengetahui faktor pendukung dan penghambat perencanaan pengembangan kurikulum; dan (4) mengetahui strategi mengatasi faktor penghambat perencanaan pengembangan kurikulum. Penelitian ini menggunakan pendekatan kualitatif untuk mendeskripsikan tentang perencanaan pengembangan kurikulum pada Kulliyatul Mu’allimien Al-Islamiyah. Rancangan penelitian yang digunakan adalah studi multi situs yang berarti menggabungkan beberapa situs, subyek, latar, dan tempat kejadian yang berlainan. Instrumen kunci adalah adalah peneliti sendiri, dengan sumber penelitian yaitu pimpinan pondok pesantren, tim pengembang kurikulum, guru, dan santri. Data diperoleh melalui observasi, wawancara, dan dokumentasi. Keabsahan data yang telah dianalisis menggunakan kriteria kredibilitas data dengan triangulasi sumber data. Hasil penelitian, bahwa perencanaan pengembangan kurikulum pada KMI ditujukan pada character building melalui micro teaching, peningkatan skill santri, dan kompetensi guru yang mengarah pada pengembangan karir guru.